Hydrogen production from glycerol dry reforming over Ag-promoted Ni/Al2O3 - Harun, N. (Elsevier Ltd, 2018)
In recent times, glycerol has been employed as feedstock for the production of syngas (H2 and CO) with H2 as its main constituent. This study centers on dry reforming of glycerol over Ag-promoted Ni/Al2O3 catalysts. Prior to characterization, the catalysts were synthesized using the wet impregnation method. The reforming process was carried out using a fixed bed reactor at reactor operating conditions; 873â1173 K, carbon dioxide to glycerol ratio of 0.5 and gas hourly space velocity (WHSV) in the range of 14.4 â¤ 72 L gcat â1 hâ1). Ag (3)-Ni/Al2O3 gave highest glycerol conversion and hydrogen yield of 40.7 and 32, respectively. The optimum conditions which gave highest H2 production, minimized methane production and carbon deposition were reaction temperature of 1073 K and carbon dioxide to glycerol ratio of 1:1. This result can attributed to the small metal crystallite size characteristics possessed by Ag (3)âNi/Al2O3, which enhanced metal dispersion in the catalyst matrix. Characterization of the spent catalyst revealed the formation of two types of carbon species; encapsulating and filamentous carbon which can be oxidized by O2. Â© 2018 Hydrogen Energy Publications LLC